2020
DOI: 10.1007/s42558-020-00030-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on epi-off crosslinking effects on porcine corneas

Abstract: Experimental inflation tests, conducted on 90 pig corneas before and after corneal collagen crosslinking (CXL) treatment, are simulated with the finite element method. The experimental sample consists of five groups of corneas treated with different UV-A irradiation times (2.5, 5, 10, 15, and 20 min) at constant irradiance 9 mW/cm2. The linear elastic shell theory is used to estimate the equivalent material stiffness of the corneas, revealing that it increases with the exposure time in CXL corneas. In the view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The finite element analysis provided at increasing irradiation doses proved that the increase in the cross-link density at a comparatively high value of irradiation dose could help improve the material strength, thus increasing the fluence not only provides an increased depth in the demarcation lines, but an increased cornea resistance that is crucial in Epi-On treatments. These clinical and experimental observations confirmed that the way to go for Epi-On CXL treatments is to find a balance between the riboflavin concentration and higher fluence between 8.1 and 10.8 J/cm 2 [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The finite element analysis provided at increasing irradiation doses proved that the increase in the cross-link density at a comparatively high value of irradiation dose could help improve the material strength, thus increasing the fluence not only provides an increased depth in the demarcation lines, but an increased cornea resistance that is crucial in Epi-On treatments. These clinical and experimental observations confirmed that the way to go for Epi-On CXL treatments is to find a balance between the riboflavin concentration and higher fluence between 8.1 and 10.8 J/cm 2 [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 61%
“…It was demonstrated [ 30 , 31 , 32 ] that the influence of CXL is characterized by a mechanism-based strain energy function, which not only explicitly depends on the density of the cross-links (as a function of the corneal thickness and UVA irradiation dose), but also relies on the discrepant distribution of cross-links in the proteoglycan matrix and along the fibers. The inflation test experimental data for the IOP-apex displacement relationships of porcine cornea at different irradiation doses of 2.7 J/cm 2 , 8.10 J/cm 2 and 10.8 J/cm 2 , respectively, showed good collimation between the predicted and simulated results, thus addressing that at the same value of IOP, the apex displacement of corneal materials after cross-linking is obviously much smaller than that without cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical behavior of the porcine cornea resembles closely the behavior of the human cornea, therefore the results of the present experimental campaign can be used to understand the response of human corneas to CXL procedure. Images of the deforming corneas taken at different pressures provide a large database of results that have been employed for further numerical elaborations [ 22 ]. Nevertheless, synthetic plots of global parameters, such as the applied pressure and the apex displacement, provide an immediate representation of the mechanical behavior and are easily interpreted, understood, and analyzed statistically; furthermore, they are comparable to other studies often synthetized in terms of inflation curves.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few anisotropic mechanical models of the porcine cornea have been derived from such experimental studies (Cornaggia et al, 2020;Elsheikh et al, 2011;Pandolfi and Boschetti, 2015). While many numerical models exist for the human cornea, numerical modeling of the porcine cornea is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…While many numerical models exist for the human cornea, numerical modeling of the porcine cornea is scarce. The few porcine models available in the literature describe the stroma with the same collagen fiber arrangement as in humans with two orthogonal fiber families (Cornaggia et al, 2020;Elsheikh et al, 2011;Pandolfi and Boschetti, 2015). This modeling approach contradicts the circular arrangement of a single family of collagen in porcine corneas observed in X-ray diffraction analyzes (Hayes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%